2022
DOI: 10.1002/lt.26399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Surveillance Biopsies in Pediatric Liver Transplantation

Abstract: Although pediatric liver transplantation (LT) results in excellent long-term outcomes, a high incidence of early acute cellular rejection and late graft fibrosis persists. Routine measurement of allograft enzymes may not reliably detect rejection episodes, identify candidates for immunosuppression minimization, or indicate allograft fibrosis. Surveillance biopsies (SBs) can provide valuable information in this regard, but their role in pediatric LT is not fully established. A retrospective cohort of 236 pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Ultimately, the report by Rocque et al (5) adds to the crescendo of data continuing to shed light on the occurrence and management of late graft changes. A livEr transplantation, vol.…”
Section: See Article On Page 843mentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, the report by Rocque et al (5) adds to the crescendo of data continuing to shed light on the occurrence and management of late graft changes. A livEr transplantation, vol.…”
Section: See Article On Page 843mentioning
confidence: 99%
“…Ultimately, the report by Rocque et al ( 5 ) adds to the crescendo of data continuing to shed light on the occurrence and management of late graft changes. A current literature review, however, shows the important contributions of HLA matching and the production of donor‐specific antibodies, neither of which were reported in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a long-standing recognition that there is poor correlation between elevation of liver blood tests and active rejection, monitoring these values continues to be the main strategy a clinician can use to suspect a rejection episode after ruling out other causes ( 6 , 7 ). Indeed, our own recent review of >800 post-LT biopsies, including >150 surveillance biopsies, showed weak correlation between liver biochemistries and rejection ( 8 ). Prior studies have attempted to identify new biomarkers of rejection in clinical LT, but these have not been able to deeply examine alloimmunity at the single cell level within the liver, due to technical limitations in working with tiny core biopsy samples [reviewed in ( 9 )].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The incidence of graft fibrosis varied considerably, from 30% to more than 90% of patients in some reports. [5][6][7][8][9][10][11][12][13][14] Inflammation and signs of rejection were also frequently reported features. 5,7,[9][10][11][12][13][14] Most of the patients included in these studies were clinically well and had normal liver biochemistry, which could be an argument in favor of performing PLB to detect occult graft injury.…”
mentioning
confidence: 99%